2022
DOI: 10.3389/fmolb.2021.735871
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analyses of the Ferroptosis-Related lncRNAs Signature for Ovarian Cancer

Abstract: Both ferroptosis and lncRNAs are significant for ovarian cancer (OC). Whereas, the study of ferroptosis-related lncRNAs (FRLs) still few in ovarian cancer. We first constructed an FRL-signature for patients with OC in the study. A total of 548 FRLs were identified for univariate Cox regression analysis, and 21 FRLs with significant prognosis were identified. The prognostic characteristics of nine FRLs was constructed and validated, showing opposite prognosis in two subgroups based on risk scores. The multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 82 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…METTL16 was reported to induce initiation or progression in leukemia [31], hepatocellular cancer [29], pancreatic cancer [30], breast cancer [32], gastric cancer [33], cervical cancer [34] and so on [35][36][37]. Zeng et al [30] demonstrated PDAC cells with high METTL16 expression increased sensitivity to PARPi, especially when combined with gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…METTL16 was reported to induce initiation or progression in leukemia [31], hepatocellular cancer [29], pancreatic cancer [30], breast cancer [32], gastric cancer [33], cervical cancer [34] and so on [35][36][37]. Zeng et al [30] demonstrated PDAC cells with high METTL16 expression increased sensitivity to PARPi, especially when combined with gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…These observations imply the existence of additional m6A methyltransferase. Recently, METTL16 (methyltransferase-like 16, also known as METT10D), which belongs to the methyltransferase like (METTL) proteins family, is identified as a novel “writer” that could drive methylation independently of the methyltransferase complex, inducing initiation or progression in hepatocellular cancer 29 , pancreatic ductal adenocarcinoma 30 , leukemia 31 , breast cancer 32 , gastric cancer 33 , cervical cancer 34 and so on 35 - 37 . In addition, Zheng et al 38 predicted that METTL16 may be a good prognostic factor for bladder cancer through bioinformatics analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the various RNA modification regulators do not function independently, and that the specific relationship between them needs further exploration. In addition, zinc finger CCCH domain‐containing protein 13 (ZC3H13), VIRMA, and methyltransferase‐like 16 (METTL16) are associated with a poor prognosis of OC (Fan et al, 2020; Zheng et al, 2021; Zhu et al, 2022). Compared with METTL3, little is known about these other m 6 A writers.…”
Section: Rna Modifications In Ocmentioning
confidence: 99%
“…Although several ferroptosis-associated lncRNAs have been analyzed for their correlation with m6A-related genes in terms of immune efficacy 115 , 116 , 117 , few studies have investigated the specific targets or pathways of m6A and ferroptosis in immune therapy. Given that ferroptosis and m6A play critical roles in tumors, further research on m6A-modified ferroptosis in diverse cancers is needed.…”
Section: The Combination Of M6a and Pcd In Cancersmentioning
confidence: 99%